Developing Scrapbook as a Medium to Improve EFL Students’ Vocabulary Mastery: A Lesson from Elementary Schools - Wulandari, Wulandari; Bulan, Arif; Rusdin, Rusdin (Journal of Language and Literature Studies, 2025)
This study was conducted to examine the feasibility of scrapbook media as a tool to enhance vocabulary mastery among elementary school students, specifically evaluating its validity, practicality, and effectiveness. The research was carried out using a Research and Development (R&D) approach, adopting the 4-D development model which includes the stages of Define, Design, Develop, and Disseminate. The participants in this study were fifth-grade students of elementary schools. Data were collected using several instruments, including validation sheets to assess content and media quality, practicality questionnaires to evaluate usability, and vocabulary mastery tests to measure learning outcomes. The validation process showed that scrapbook media is highly valid, with content validation reaching 91.11% and media validation at 90%, indicating strong alignment with learning objectives and media standards. Furthermore, the media demonstrated practical applicability in classroom settings and showed effectiveness in improving students’ vocabulary acquisition, as evidenced by an effectiveness rate of 69.83%. These results support the conclusion that scrapbook media is a feasible and impactful tool for vocabulary instruction in elementary schools. Its creative and engaging format offers an alternative learning medium that can motivate students and support language learning. The implication of this study suggests that educators and curriculum developers should consider incorporating scrapbook-based learning media as part of innovative teaching strategies, particularly for language subjects in early education.